2020
DOI: 10.3389/fphys.2020.570441
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin Ameliorates LPS-Induced Cardiac Dysfunction by SIRT1-Dependent Inhibition of NLRP3 Inflammasome

Abstract: Shikonin (SHI) is an anti-inflammatory agent extracted from natural herbs. It is still unknown whether SHI ameliorates lipopolysaccharide (LPS)-induced cardiac dysfunction. This study aims to explore the protective effects of SHI on LPS-induced myocardial injury and its mechanism. The LPS-induced cardiac dysfunction mouse model was employed to investigate the protective effects of SHI. In the present study, we found that SHI treatment improved the survival rate and cardiac function and remarkably ameliorated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 41 publications
(49 reference statements)
3
20
0
Order By: Relevance
“…For example, shikonin was shown to be capable of alleviating LPS-induced renal injury and oxidative damage [ 250 ], high glucose-induced renal tubular epithelial cell injury in vitro [ 251 ], and unilateral ureteral obstruction (UUO)-induced tubular apoptosis and macrophage infiltration [ 252 ]. Similar findings were obtained in experimental models of cardiac dysfunction [ 253 ], acute lung [ 254 , 255 , 256 ], liver [ 257 , 258 , 259 , 260 , 261 , 262 ], and ear injuries [ 263 ]. Shikonin also protected against cerebral ischemia/reperfusion- and autoimmune encephalomyelitis-induced brain injury through reducing oxidative stress [ 264 , 265 ] and protected microglial cells against LPS-induced cell death [ 266 ] ( Figure 4 B ).…”
Section: Emerging Areas Of Research Involving Pkm2supporting
confidence: 78%
“…For example, shikonin was shown to be capable of alleviating LPS-induced renal injury and oxidative damage [ 250 ], high glucose-induced renal tubular epithelial cell injury in vitro [ 251 ], and unilateral ureteral obstruction (UUO)-induced tubular apoptosis and macrophage infiltration [ 252 ]. Similar findings were obtained in experimental models of cardiac dysfunction [ 253 ], acute lung [ 254 , 255 , 256 ], liver [ 257 , 258 , 259 , 260 , 261 , 262 ], and ear injuries [ 263 ]. Shikonin also protected against cerebral ischemia/reperfusion- and autoimmune encephalomyelitis-induced brain injury through reducing oxidative stress [ 264 , 265 ] and protected microglial cells against LPS-induced cell death [ 266 ] ( Figure 4 B ).…”
Section: Emerging Areas Of Research Involving Pkm2supporting
confidence: 78%
“…Recent studies have demonstrated that herbal Chinese medicines are therapeutic against cardiovascular diseases. For example, Shikonin (extracted from Chinese herb radix arnebiae) ameliorated cardiac dysfunction and inhibited the activation of NLRP3 inflammasome in lipopolysaccharide (LPS)induced cardiac dysfunction (Guo et al, 2020). Additionally, Songorinea (napelline-type C 20 -diterpene alkaloid in Aconitum carmichaelii Debx.)…”
Section: Introductionmentioning
confidence: 99%
“… 33 Shikonin, a traditional Chinese medicine extract, improved LPS-induced sepsis cardiac dysfunction by SIRT1. 34 We predicted that SIRT1 was the target gene of miR-486-5p through the online biological software miRDB, and miR-486-5p targeting SIRT1 has been demonstrated in non-small cell lung cancer 35 and myocardial ischemia-reperfusion injury. 36 Therefore, we speculate that miR-486-5p may be involved in the progress of sepsis by targeting SIRT1.…”
Section: Discussionmentioning
confidence: 99%